2009
DOI: 10.1108/09596110910975972
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of customer verbal aggression among hotel employees

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
126
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 70 publications
18
126
0
3
Order By: Relevance
“…In a study of students on supervised work experience in the United Kingdom (UK), Worsfold and McCann (2000) also observed that employees may think they need to flirt or behave sexually at work, which may be reciprocated by customers. Management's high expectations of customer satisfaction can explicitly condone difficult customer behaviours, particularly in settings that offer both alcohol and anonymity (Worsfold and McCann, 2000, Pritchard and Morgan, 2006, Poulston, 2008a, Karatepe et al, 2009) such as many bars and nightclubs. Sadaraka et al's (2015) study extended Folgerø and Fjeldstad's (1995) work by showing that female dancers in the Cook Islands gradually changed their attire to become more sexually provocative, to fit in with the norms of the dancing group.…”
Section: Influences On Sexual Harassment In the Workplacementioning
confidence: 99%
“…In a study of students on supervised work experience in the United Kingdom (UK), Worsfold and McCann (2000) also observed that employees may think they need to flirt or behave sexually at work, which may be reciprocated by customers. Management's high expectations of customer satisfaction can explicitly condone difficult customer behaviours, particularly in settings that offer both alcohol and anonymity (Worsfold and McCann, 2000, Pritchard and Morgan, 2006, Poulston, 2008a, Karatepe et al, 2009) such as many bars and nightclubs. Sadaraka et al's (2015) study extended Folgerø and Fjeldstad's (1995) work by showing that female dancers in the Cook Islands gradually changed their attire to become more sexually provocative, to fit in with the norms of the dancing group.…”
Section: Influences On Sexual Harassment In the Workplacementioning
confidence: 99%
“…Their findings suggest that regarding service recovery performance organisational support is more efficient when one differentiates between high-and low-performing frontline employees. Karatepe et al (2009) found the emotional dissonance and emotional exhaustion among hotel employees to be significant outcomes of customer verbal aggression. Recent studies have also found that emotional exhaustion (Karatepe et al, 2009) and surface acting (Kim et al, 2012), referring to faking the expected emotions, decreased service recovery performance.…”
Section: Employee Recoverymentioning
confidence: 96%
“…Karatepe et al (2009) found the emotional dissonance and emotional exhaustion among hotel employees to be significant outcomes of customer verbal aggression. Recent studies have also found that emotional exhaustion (Karatepe et al, 2009) and surface acting (Kim et al, 2012), referring to faking the expected emotions, decreased service recovery performance. To the contrary, frontline hotel employee emotional intelligence and genuine attempts to experience positive emotions (Kim et al 2012), as well as perceived organisational support (Karatepe, 2012), have been found to relate positively and increase the service recovery performance.…”
Section: Employee Recoverymentioning
confidence: 96%
See 2 more Smart Citations